Survey of users’ perceptions of clinical microbiology laboratory services in Nigeria (2012)
Background:The Clinical Microbiology laboratory is expected to adequately measure and monitor its performance by actively and routinely soliciting from its clients their level of satisfaction with services received and use the information to develop processes that meet customer’s needs. This survey was done in order to objectively identify some of the challenges faced by laboratory end users in Nigeria with a view to proffering feasible solutions to such problems. Methods: Semi –structured, pre-tested Questionnaires administered to laboratory users in 2 teaching hospitals in Nigeria to find out their level of satisfaction with various aspects of laboratory services. One is a Federal Government hospital with 620 bed spaces and 7 full time Consultant Clinical Microbiologists while the other hospital is owned by State Government and has 280 bed spaces, 1 full time plus 2 visiting Consultant Clinical Microbiologists. Results: There is a general low level customer satisfaction observed in this study. Only 27.8% and 5.4% of respondents from UCH and LTH respectively agreed that laboratory user’s handbook was available while about 38.3% and 22.5% respectively agreed that laboratory turnaround time was satisfactory. Respondents from UCH and LTH who agreed that it was easy to obtain expert advice from Consultant Clinical Microbiologists were 45.1% and 20.2% respectively. About 94.7% and 88.8% of respondents from UCH and LTH respectively agreed that request forms were easy to fill while 76.7% and 68.5% respectively agreed that expert advice obtained from Consultant Clinical Microbiologists were helpful in the management of their patients. Discussion, conclusion and recommendation: The general low level of customer satisfaction observed from the 2 hospitals may be attributable to the general inadequate health workforce and infrastructure in Nigeria where the government spend only 6.4% of its annual budget on health which is far below expectation. The particularly lower level of customer satisfaction in LTH may be due to the fact that there is only one full time Clinical Microbiologist in the in the laboratory. These laboratories can make the best out of the situation at hand by improving their communication with the users so as to make them appreciate the actual cost of tests andtime required to generate results.